2023
DOI: 10.1109/access.2023.3279720
|View full text |Cite
|
Sign up to set email alerts
|

Affect Recognition in Muscular Response Signals

Abstract: This study investigated the potential of recognising arousal in motor activity collected by wristworn accelerometers. We hypothesise that emotional arousal emerges from the generalised central nervous system which embeds affective states within motor activity. We formulate arousal detection as a statistical problem of separating two sets -motor activity under emotional arousal and motor activity without arousal. We propose a novel test regime based on machine learning assuming that the two sets can be distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…However, according to the Nyquist–Shannon sampling theorem, the sampling rate needs to be twice the frequency of the original signal to obtain full resolution. 29 Consequently, with 10 Hz recordings, some information is lost, possibly causing a more fragmented stepwise CAC, reporting additional change points. In our case, the 10 Hz sampling frequency was chosen strictly to minimize the battery load and increase maximum recording time, ensuring study feasibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to the Nyquist–Shannon sampling theorem, the sampling rate needs to be twice the frequency of the original signal to obtain full resolution. 29 Consequently, with 10 Hz recordings, some information is lost, possibly causing a more fragmented stepwise CAC, reporting additional change points. In our case, the 10 Hz sampling frequency was chosen strictly to minimize the battery load and increase maximum recording time, ensuring study feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…A technological study of accelerometer-equipped soccer supporters found significant differences between periods containing goals to non-event periods in the match, analyzing high resolution uncompressed actigraphy data. 29 Likewise, causality between fear and behavioral pattern changes have been observed in studies of laboratory mice. 28 This evidence supports the hypothesis proposed in a systematic review on activation in bipolar disorder; 5 namely, that motor activity can be considered an objective observation of the inner psychological state expressed in behavior patterns.…”
Section: Introductionmentioning
confidence: 93%